Sikh history from Persian sources : translations of major texts - Grewal, J. S.; Habib, Irfan, 1931-; Indian History Congress. Session 1999 : Calicut University) (New Delhi : Tulika, 2001)
Papers presented at sixtieth session of Indian History Congress at Calicut University on December 29, 1999.
"Khalsa tercentenary celebration."
Includes bibliographical references and index.
Keywords: Sikhs -- History